2018
DOI: 10.1002/ange.201711418
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Nano‐Ferrierite along the 10‐Ring‐Channel Direction Boosts Their Catalytic Behavior

Abstract: Ferrierite zeolites with nanosized crystals and external surface areas higher than 250 m 2 ·g -1 have been prepared at relatively low synthesis temperature (120ºC) by means of the collaborative effect of two Organic Structure Directing Agents (OSDA). In this way, hierarchical porosity is achieved without the use of post-synthesis treatments that usually involve leaching of T atoms and solid loss. Adjusting the synthesis conditions it is possible to decrease the crystallite size in the directions of the 8-and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…The long carbon chain in the surfactant limited the crystal growth of FER zeolites along three dimensions, and thus produced the aluminosilicate FER nanocrystals with sizes in the range of 10-20 nm ( Figure 4A). Because of the reduction of crystal size along the [001] direction, the access to Brønsted acid sites increased, which enhanced its catalytic activity as well as lifetime in oligomerization of 1-pentene to liquid fuels reaction ( Figure 4B) [7]. Very similarly, Xu et al reported a successful size control strategy of aluminosilicate FER zeolite by adding cetyltrimethyl ammonium bromide (CTAB) into the synthesis system containing Pi as the organic template.…”
Section: Morphology Control Strategies Of Aluminosilicate Fer Zeolitementioning
confidence: 94%
See 1 more Smart Citation
“…The long carbon chain in the surfactant limited the crystal growth of FER zeolites along three dimensions, and thus produced the aluminosilicate FER nanocrystals with sizes in the range of 10-20 nm ( Figure 4A). Because of the reduction of crystal size along the [001] direction, the access to Brønsted acid sites increased, which enhanced its catalytic activity as well as lifetime in oligomerization of 1-pentene to liquid fuels reaction ( Figure 4B) [7]. Very similarly, Xu et al reported a successful size control strategy of aluminosilicate FER zeolite by adding cetyltrimethyl ammonium bromide (CTAB) into the synthesis system containing Pi as the organic template.…”
Section: Morphology Control Strategies Of Aluminosilicate Fer Zeolitementioning
confidence: 94%
“…Zeolites are crystalline microporous materials which have been widely applied on an industrial scale in heterogeneous catalysis, adsorption, separation and ion exchange in the past decades [1][2][3][4][5]. Among them, Ferrierite (FER) zeolite is one of the industrialized types, which has excellent catalytic properties in skeletal isomerization of n-alkene, methanol to olefin, N 2 O decomposition, CO 2 hydrogenation, dehydration of methanol or ethanol, dimethyl ether carbonylation, and so on [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance mass transfer, great efforts have been made for improving mass transfer in SSZ-39 zeolites such as generation of mesoporosity and preparation of SSZ-39 nanocrystals. 5,45–54…”
Section: Ssz-39 Zeolite Synthesismentioning
confidence: 99%
“…FER zeolite is a medium-pore zeolite containing 10-Membered Ring (10-MR) channels (0.42 × 0.54 nm) in the [001] direction and 8-MR channels (0.35 × 0.48 nm) in the [010] direction [25][26][27][28][29][30][31]. Aluminosilicate FER zeolite, which is represented by ZSM-35, shows distinguished catalytic performances in many reactions, such as skeletal isomerization, high-olefin catalytic cracking, carbonylation of dimethyl ether, methanol to olefins, and NO x reduction [25,26,[32][33][34][35][36][37][38][39][40] To further enhance the catalytic performance, the preparation methods for aluminosilicate FER zeolites with controllable morphology and crystal sizes are particularly attractive. Corma et al prepared FER nanocrystals with sizes of 10-20 nm using piperidine and surfactant as dual templates [25].…”
Section: Of 10mentioning
confidence: 99%
“…Aluminosilicate FER zeolite, which is represented by ZSM-35, shows distinguished catalytic performances in many reactions, such as skeletal isomerization, high-olefin catalytic cracking, carbonylation of dimethyl ether, methanol to olefins, and NO x reduction [25,26,[32][33][34][35][36][37][38][39][40] To further enhance the catalytic performance, the preparation methods for aluminosilicate FER zeolites with controllable morphology and crystal sizes are particularly attractive. Corma et al prepared FER nanocrystals with sizes of 10-20 nm using piperidine and surfactant as dual templates [25]. Meanwhile, FER nanoneedles with a diameter of 10 nm were developed by adding choline as an organic template [41].…”
Section: Of 10mentioning
confidence: 99%